Complement C3 participation in monocyte adhesion to different surfaces. - McNally, A K (1994)
As part of an ongoing investigation into the role of the monocyte/macrophage in biocompatibility, a major goal is to identify the adhesion mechanisms that initiate and promote the observed in vivo morphologic progression of monocyte-to-macrophage-to-foreign body giant cell on biomaterials. We have exploited differently modified polystyrenes, specific component-depleted sera, and monoclonal antibodies (mAbs) to leukocyte integrins to ask what adhesion mechanisms mediate human blood monocyte adhesion to different surfaces in vitro. Preliminary findings are that monocyte interactions with fluorinated, siliconized, nitrogenated, and oxygenated surfaces are reduced by 50-100% when complement component C3-depleted serum is used for adsorption; reductions vary with material surface properties. Adhesion is restored on all surfaces when C3-depleted serum is replenished with purified C3. Monocyte adhesion to serum-adsorbed surfaces is inhibited by mAbs to the leukocyte integrin beta subunit, CD18 (mAbs 60.3 and MHM23), and partially inhibited by a mAb to the alpha subunit, CD11b (mAb 60.1), suggesting adhesive interactions between adsorbed C3bi (the hemolytically inactive form of the C3b fragment) and the leukocyte integrin CD11b/CD18. However, adsorbed fibrinogen reduces the effectiveness of these mAbs, indicating that alternative adhesion mechanisms may operate depending on the propensities of critical adhesion-mediating components to be adsorbed onto different surfaces.